HEPATOPROTECTIVE EFFECT OF BLACK CUMIN (Nigella sativa) AGAINST THE LIVER Aspartame-induced Rattus norvegicus BASED ON HISTOPATHOLOGICAL FEATURES - Mukharomah, Katrine Adiansyah Dwi; Sayekti, Fitria Diniah Janah (Jurusan Teknologi Laboratorium Medis, Poltekkes Kemenkes Denpasar, 2024)
Foods and beverages containing artificial sweeteners in the form of aspartame are widely consumed in various countries including Indonesia, and have increased every year. Excessive consumption of aspartame can increase the occurrence of hepatotoxicity in the liver such as changes in the histopathological picture of the liver characterized by degeneration and cell necrosis (cell death). Hepatoprotectors are compounds that have antioxidant benefits so that they can protect the liver by reducing oxidation reactions in liver damage. One compound that functions as a hepatoprotector is black cumin (Nigella sativa). Aims: This study aims to determine the effect of black cumin administration on macroscopic and microscopic observations of liver organs in male white rats induced by aspartame. Methods: This study was experimental with 5 treatment groups including 1 normal group, 1 negative group and 3 aspartame and black cumin treatment groups. Liver tissue is observed macroscopically based on color, texture and size, while microscopically it is done by assessing the presence of normal cells, degeneration and necrosis. The results. The results of microscopic observations showed that the negative control and treatment groups showed cell damage in the form of cell degeneration and necrosis. The results of the study based on the ANOVA test obtained a significance value of 0.05 which means there is an average difference between groups and continued with the Tukey test. Conclusions: Based on Tukey's test, the fourth group (K4) is a treatment group with the most effective dose of black cumin in preventing liver cell damage to white rats, which is 0.2 ml / 200 g body weight / day.